Penerapan Media Pembelajaran Fipbook Berbasis TPACK pada Pembelajaran Tema 4 Kelas IV SD Hang Tuah 10 Juanda - Delfita Nur Aprilutfi; Apri Irianto; Susi Hermin Rusminati (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstrakPenelitian ini dilatarbelakangi oleh kurangnya minat mahasiswa terhadap pelaksanaan kegiatan pembelajaran daring. Pembelajaran daring akan lebih menarik jika Anda menggunakan media. Media yang digunakan adalah media pembelajaran flipbook berbasis tpack. Media pembelajaran flipbook berbasis TPACK merupakan media yang memanfaatkan perkembangan teknologi dan memberikan pengalaman belajar yang menarik, khususnya pada pembelajaran tema. Tujuan dari penelitian ini adalah untuk mendeskripsikan penerapan dan respon siswa terhadap pembelajaran tema 4 dengan menggunakan media pembelajaran flipbook berbasis TPACK pada siswa kelas IV SD Hang Tuah 10 Juanda. Penelitian ini menggunakan penelitian kualitatif deskriptif. Data berupa observasi mahasiswa, kuesioner respon mahasiswa, dan wawancara mahasiswa.Â AbstractThis research was motivated by the lack of interest of students in the implementation of online learning activities. Online learning will be more interesting if you use media. The medium used is tpack-based flipbook learning media. TPACK-based flipbook learning media is a medium that utilizes technological developments and provides an interesting learning experience, especially on theme learning. The purpose of this study is to describe the application and response of students to theme 4 learning using TPACK-based flipbook learning media in grade IV students of Hang Tuah 10 Juanda Elementary School. This study uses descriptive qualitative research. Data in the form of student observations, student response questionnaires, and student interviews. The source of this research data is 26 students in Hang Tuah Elementary School 10 Juanda. This research data analysis technique uses data reduction, data presentation, and conclusion withdrawal. The validity of this research data uses triangulation techniques. The results of this study describe the application of flipbook learning media successfully done, students are able to do theme 4 learning very well, the student response is good in using flipbook learning media on theme 4. Students look more active and motivated as learning progresses.Keywords: TPACK-based flipbook learning media, theme learning